IMPLEMENTATION OF REGULATION OF THE COORDINATING MINISTER FOR ECONOMIC AFFAIRS NUMBER 1 OF 2022 IN DISTRIBUTING COLLATERAL-FREE PEOPLE'S BUSINESS CREDIT TO CUSTOMERS IN BENGKULU CITY - Ganefi; Wafiya; Nurhani Fithriah (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
To accelerate the National Economic Recovery (PEN), one of them is assistance in distributing credit for Micro, Small, and Medium Enterprises (MSMEs); for this reason, the government has issued a People's Business Credit (KUR) regulation with a loan ceiling twice as high as previously IDR 10 million to IDR 50 million, IDR 50 to 100 million and IDR 100 million to IDR 500 million. as well as KUR loans for unmarried people with a maximum loan ceiling of IDR 10 million. Based on PERMENKO No. 1, the year 2022, the government issued a policy, namely, the distribution of People's Business Credit (KUR) loan assistance for Micro, Small, and Medium Enterprises (MSMEs), that the loan requirements are carried out without collateral. However, in its implementation in the field, the government's policy turns out that the creditor/bank still requires that the People's Business Credit (KUR) loan carried out by MSMEs still use additional collateral, including a loan of IDR 10 million, at least one motorbike BPKB. For IDR 50 million, the collateral is one car, BPKB, or land/house certificate. Only then, after the issuance of PERMENKO No. 1 of 2023, did the Bank completely exempt KUR recipients from the additional collateral requirements in Bengkulu City. Keywords: Collateral Implementation, Banks, MSMEs